Development Internal Problems of Shanghay Cooperation Organization - O. Y. Kolegova (Vestnik MGIMO-Universiteta)
The article analyzes the main internal problems of the Shanghai Cooperation Organization. Particular attention is paid to the conflict of interests of the participating countries, as well as identifying obstacles to strengthen the organization and increase its influence in the international arena. The international organizations are created by the states to meet mutual problems in the course of interstate relations requiring regular cooperation mechanism. Given the background of the Organization, it is important to emphasize that the main reason for the establishment of the Shanghai organization was the need for the united front against the strengthening of the region at the turn of centuries against dangerous trends of terrorism, extremism, separatism, the growth of organized crime. Despite the conflict of interests and the internal and external development challenges thirteen-year history of evolution of the SCO, to some extent proves its effectiveness, moreover, there are the preconditions for its consistent transition to a more comprehensive organization.